Aru Shah and the end of time - Chokshi, Roshani (Los Angeles : Disney Hyperion, 2018)
Twelve-year-old Aru stretches the truth to fit in at her private school, but when she is dared to prove an ancient lamp is cursed, she inadvertently frees an ancient demon.
School Library Journal starred, March 2018
Pub Weekly, December 2017
Kirkus Starred, February 2018
5.3.
3-6.
OBOB 2019-2020.
Keywords: Supernatural -- Fiction; Demonology -- Fiction; Blessing and cursing -- Fiction; Antiquities -- Fiction; Museums -- Fiction; Honesty -- Fiction; Hindu mythology; Hindu mythology -- Juvenile fiction